CA-RICH GARNET-CLINOPYROXENE ROCKS AT HUJIALIN IN THE SU-LU TERRANE (EASTERN CHINA): DEEPLY SUBDUCTED ARC CUMULATES? - Yang J.-J. (My University, 2006)
Layers of Ca-rich garnet-clinopyroxene rocks enclosed in a serpentinite body at Hujialin, in the Su-Lu terrane of eastern China, preserve igneous textures, relict spinel in garnet, and exsolution lamellae of Ca-rich garnet, ilmenite/magnetite, Fe-rich spinel, and also amphibole in clinopyroxene. In terms of their major and trace element compositions, the studied samples form a trend from arc cumulates towards Fe-Ti gabbros. Reconstructed augite compositions plot on the trend for clinopyroxene in arc cumulates. These data suggest that the rocks crystallized from mantle-derived magmas differentiated to various extents beneath an arc. The Ca-rich garnet + diopside assemblage is inferred to have formed by compressing Ca-rich augite, whereas the relatively Mg-rich cores of garnet porphyroblasts may have formed at the expense of spinel. The protolith cumulates were subducted from near the crust-mantle boundary (c. 1 GPa) deep into the upper mantle (4.8 ± 0.6 GPa and 750 ± 50°C). Negatively sloped P-T paths for the garnet-clinopyroxene rocks and the corollary of corner flow induced subduction of mantle wedge peridotite are not supported by the available data. Cooling with, or without, decompression of the cumulates after the igneous stage probably occurred prior to deep subduction. © 2006 Oxford University Press.
Keywords: ARC CUMULATES; CA-RICH GARNET; GARNET-CLINOPYROXENE ROCKS; SULU TERRANE; UHP METAMORPHISM